Electrochemiluminescence at 3D Printed Titanium Electrodes - Douman, Samantha F.; De Eguilaz, Miren Ruiz; Cumba, Loanda R.; Beirne, Stephen; Wallace, Gordon G.; Yue, Zhilian; Iwuoha, Emmanuel I.; Forster, Robert J. (Frontiers in Chemistry, 2021)
The fabrication and electrochemical properties of a 3D printed titanium electrode array are described. The array comprises twenty-five round cylinders (0.015 cm radius, 0.3 cm high) that are evenly separated on a 0.48 cm x 0.48 cm square porous base (total geometric area of 1.32 cm2). The electrochemically active surface area consists of fused titanium particles and exhibits a large roughness factor 17. In acidic, oxygenated solution, the available potential window is from approximately -0.3 V to +1.2 V. The voltammetric response of ferrocyanide is quasi-reversible arising from slow heterogeneous electron transfer due to the presence of a native/oxidatively formed oxide. Unlike other metal electrodes, both [Ru(bpy)3]1+ and [Ru(bpy)3]3+ can be created in aqueous solutions which enables electrochemiluminescence to be generated by an annihilation mechanism. Depositing a thin gold layer significantly increases the standard heterogeneous electron transfer rate constant, ko, by a factor of approximately 80 to a value of 8.0±0.4x10-3 cm s-1 and the voltammetry of ferrocyanide becomes reversible. Both the native titanium and gold coated arrays generate electrochemiluminescence using tri-propyl amine as a co-reactant, but the intensity of the gold-coated array is between 30 (high scan rate) and 100-fold (slow scan rates) higher at the gold coated arrays. Moreover, while the voltammetry of the luminophore is dominated by semi-infinite linear diffusion, the ECL response is significantly influenced by radial diffusion to the individual microcylinders of the array.